Analysis of Internal Leakages of Residential Ventilation Units by various test methods - Moser, Marie-Teres; Halfvardsson, Anneli; Chlup, Jaroslav; Huber, Heinrich (CLIMA 2022 conference, 2022)
Internal leakages of bidirectional residential ventilation units (RVU) have a negative impact on hygiene and energy efficiency. Therefore, internal leakages are an essential part of the European standards and should be a requirement and part of the energy labelling in the revision of Regulation EU 1253/2014. The current test standard defines a static pressure method intended for RVUs with plate heat exchangers. In addition, there is an in-duct method and a chamber method, using tracer gas, for air handling units (AHU) with rotary heat exchangers. The Eurovent Product Group Residential Air Handling Units launched a project to analyse these methods. The project was also supported by the Swiss Federal Office of Energy and GebäudeKlima Schweiz. Two AHUs, one with plate heat exchangers and the other with rotary heat exchanger, were tested with all three methods. The finding was that the results of the different methods were not comparable. A Master's study confirmed this with a third RVU. Hence, a new method was introduced, the so-called Advanced Pressure Method (APM). This approach allows testing without tracer gas, but with comparable results to the in-duct method. The APM is based on a node model of the flow paths within the RVU. All in all, the APM is a reliable approach to determine the internal leakage, even though the measurement uncertainty is higher than with the in-duct method. The accuracy is limited due to the sensitivity of the mathematical model. Therefore, the APM has been proposed for the use of the APM in manufacturers' laboratories. Furthermore, in the EN 13142 standard, the internal leakage is used to correct the temperature efficiency. The current test standard leads to results that depend not only on the quality of an RVU, but also on the test method. In addition, test conditions that are not clearly defined, e.g. rotary speed, have an effect. The project is intended to open the discussion on the three mentioned test standards and their influence on energy labelling.